Hey there! :)
Answer:
First option: As x⇒ ∞ f(x) ⇒ -∞. As x⇒ -∞ f(x) ⇒ ∞.
Step-by-step explanation:
Rearrange the equation:
f(x) = -x³ - 2x² + 1
This is a negative cubic function. The function decreases over the interval
(-∞, ∞). Therefore:
As x⇒ ∞ f(x) ⇒ -∞.
As x⇒ -∞ f(x) ⇒ ∞.
This is the first option.
Answer:
x = -4
Step-by-step explanation:
2x² + 8x = x² - 16
x² + 8x + 16 = 0
x² + 4x + 4x + 16 = 0
x(x + 4) + 4(x + 4) = 0
(x + 4)² = 0
x = -4
Answer:I am pretty sure it is A
Step-by-step explanation: